Ocena primernosti bukove žagovine kot ojačitvene komponente pri pripravi termoplastičnih biokompozitov - Zule, Janja (Acta silvae et ligni, 2016)
Beech sawdust was used as reinforcing component for the preparation of biocomposites with polyoxymethylene % POM and polylactic acid % PLA as polymer matrix. Materials with different portions of sawdust, e.g. 5, 10 and 15 wt. %, were prepared by using extrusion and injection techniques. Their mechanical (E modulus, flexural and tensile strength and strain) as well as thermal (melting point, glass transition) properties were determined. The results indicate that sawdust acts as reinforcement of the composites in the case of flexural stress and also tensile strength by POM matrix. Addition of sawdust to POM and PLA increases maximal temperature of biocomposite utilization. The main advantage of new materials is low density. Despite their brittleness they are convenient, low-cost alternatives to composites reinforced with glass fibres.
Keywords: beech sawdust; bukova žagovina; biocomposites; biokompoziti; polioksimetilen; polyoxymethylene; polylactic acid; polimlečna kislina; ekstruzija; extrusion; injection; brizganje; mechanical properties; mehanske lastnosti; termične lastnosti; thermal properties